The probable impact of policies and policy measures on globalisation - Losoncz, Miklós (Competitio, 2024)
This paper aims to identify the impact of the recent economic and non-economic shocks on the globalisation of trade in terms of trade policy and structural openness, and to take a side in the discussion about the reversal, the slowdown, and the continuation of trade globalisation. The report argues that geopolitical decisions based on pure political priorities and different macro- and micro-policies may harm trade globalisation temporarily. Nevertheless, in the long run, underlying economic factors, such as decreasing trade costs and expanding services trade remain the critical driving forces of globalisation. The speed of the process is likely to be slower than before, and its characteristics are different. With weakening multilateralism and increasing fragmentation, the emerging global world order will be suboptimal from the point of view of economic efficiency. Journal of Economic Literature (JEL) codes: F01, F02, F13, F60.